Control prenatal como factor predictor de morbimortalidad del recién nacido en el Hospital General Isidro Ayora de Loja. - Ortega Zhunaula, Edison Stalin (2017)
In order to correlate the number of prenatal controls and morbidity and mortality of the newborn, this study was carried out at the Hospital Isidro Ayora de Loja, in a descriptive type, for which 150 cases of newborns who met the criteria of inclusion, during the period April-September 2016, in which the following variables were studied: maternal risk factors (number and time of onset of prenatal control), anthropometric data, APGAR and cause of morbidity and mortality. From the information gathered, it was obtained that about 80% of the mothers who had adequate number of controls and the first prenatal appointment before twenty weeks presented optimal results in the health of the newborn while the opposite happens when these prenatal control conditions do not are fulfilled being the female population the most incident. In more than 50% of pregnancies with optimal prenatal control it was evidenced that the gestation product was born at term with normal weight and in welfare conditions; pregnancies that did not meet the standards of prenatal control had high percentages of preterm infants, with low birth weight and cases of moderate to severe depression. Likewise, pregnancies with optimal prenatal control show low rates of morbidity and mortality in the newborn. The main causes of admission to Neonatology were of metabolic, septic and respiratory origin. The main causes of mortality of the newborn are prematurity, of respiratory and septic origin. Key words: prenatal control, newborn, newborn morbidity, newborn mortality.